The Effect Of Natural Dye Extract From Beetroot (Beta Vulgaris L.) On The Quality Of Lip Tint Cosmetic Products - Hidayat, Dinnisa Haura Zhafira; Asy'ari Muhammad Fahmi; Fathan Mubiyna; Citra Ayu Maharani Permata Suri; Muhammad Bagaskara; Anisa Farah Maharani (Jurnal EduHealth, 2024)
The use of lip tint is highly popular among women. However, lip tints that are popular for their aesthetics often contain ingredients that pose health risks such as Tartrazine, Methylparaben, Propylparaben, and Rhodamine B. To address this issue, the use of fruits as alternative cosmetic ingredients becomes an interesting solution. By utilizing beetroot (Beta vulgaris L.) extract as an option to replace dyes in lip tint, the same effective color can be obtained as with synthetic or conventional ingredients but with more natural properties. Beetroots are fruits rich in vitamin E and have red flesh. The vitamin and pigment content can help lips achieve a natural red color and prevent dryness.Therefore, research on beetroot extract processing is needed to increase public awareness of the potential for safer and higher-quality cosmetic ingredients for consumers.